Edukasi Literasi Financial Technology (Fintech) bagi Masyarakat Kampung Baru, Kelurahan Oesao Berbasis Praktik Nyata - Antonius Andrias Reis Tanesi; Elexsi Y.B Poyk; Dorianci Puay; Anisa Leonita P. Mone Kadja (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
This Community Service was carried out in Kampung Baru,jalan Timor Raya KM 8 Kelurahan Oesao,kecamatan Kupang Timur. Kabupaten Kupang on June 16, 2025 with the aim of increasing public understanding of Financial Technology (FinTech) as part of digital financial literacy. The activity began with a pre-test to identify the community's initial knowledge, continued with the delivery of material through an interactive lecture method, a simulation of the digitalization of the payment system using QRIS, and ended with a post-test and a question and answer session. The material presented included the basic concepts of FinTech, types of digital financial services, digital security, and the benefits and risks of using financial technology. The community showed high enthusiasm, as evidenced by active participation in the discussion and increased understanding based on the results of the post-test evaluation. This PKM activity has a positive impact in raising public awareness and readiness to face the increasingly rapid digital transformation in the financial sector in the future. As a follow-up, the community is expected to be able to learn and utilize FinTech wisely in everyday life, especially in digital transactions and personal financial management.